Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1155/2013/210205
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Significances of Contactin-1 in Human Gastric Cancer

Abstract: Background. This study aimed at determining the relationship between vascular endothelial growth factor-C (VEGF-C), vascular endothelial growth factor receptor-3 (VEGFR-3), and contactin-1 (CNTN-1) expression in gastric cancer (GC). Methods. The expression level of CNTN-1 mRNA and CNTN-1 protein of 33 cases was determined using RT-PCR and Western Blot. And 105 cases were immunohistochemically examined for VEGF-C, VEGFR-3, and CNTN-1 expressions. Assessment of lymphatic vessel density (LVD) was also performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…CNTN-1, a glycosyl phosphatidylinositol NCAM, was found to play important roles not only in nervous system development [17,18,30] but also in the invasion and metastasis of lung adenocarcinoma [19,31,32] and other tumours [20,22,23]. This study was performed to investigate whether CNTN-1 is associated with MDR in lung adenocarcinoma, and the findings revealed that CNTN-1 plays an important role in MDR of lung adenocarcinoma besides invasion and metastasis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CNTN-1, a glycosyl phosphatidylinositol NCAM, was found to play important roles not only in nervous system development [17,18,30] but also in the invasion and metastasis of lung adenocarcinoma [19,31,32] and other tumours [20,22,23]. This study was performed to investigate whether CNTN-1 is associated with MDR in lung adenocarcinoma, and the findings revealed that CNTN-1 plays an important role in MDR of lung adenocarcinoma besides invasion and metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent study revealed that CNTN-1 was associated with invasive ability and to inversely correlate with the prognosis of lung adenocarcinoma patients, and it was proposed to function in the invasion and metastasis of lung adenocarcinoma cells via RhoA-mediated mechanisms [19]. Studies in oesophageal squamous cell carcinoma [20,21], oral squamous cell carcinoma [22], and gastric cancer [23] further confirmed that CNTN-1 plays a critical role in the development, progression, and pathogenesis of these tumours.…”
mentioning
confidence: 95%
“…Recently, CNTN-1 was demonstrated to be able to promote invasion, metastasis and proliferation in prostate cancer [43], thyroid cancer [44], gastric cancer [35, 45-46], lung cancer [32-33], esophageal squamous cancer [30, 47], and oral squamous cancer [31]. Additionally, in our previous studies, CNTN-1 was found to enhance the metastasis, invasion, and chemoresistance of lung cancer cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on identifying molecular markers and developing related active treatment methods for gastric cancer. Efforts have been made to identify biomarkers for predicting survival or recurrence in gastric cancer (Wang et al, 2013;Sezer et al, 2013;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%